Towards Sustainable Accountability And Transparency In Public Sector: Case Study of Pusat Investasi Pemerintah With GRI Standards - Dini Salamah; Melia Famiola; Muhammad Yusuf (Journal Integration of Management Studies, 2025)
As a signatory to the United Nations' 2030 Sustainable Development Goals (SDGs), Indonesia mandates active governmental engagement in advancing sustainability. This study investigates the readiness of the Pusat Investasi Pemerintah (PIP)—a Public Service Agency under the Ministry of Finance—to institutionalize Environmental, Social, and Governance (ESG) principles and align its sustainability reporting with the Global Reporting Initiative (GRI) Universal Standards 2021. Employing a qualitative approach, the research applies gap analysis to evaluate PIP's existing practices against 30 GRI 2 metrics. Data collection involved semi-structured interviews with 11 key management figures and document analysis of internal reports and regulatory frameworks. Findings reveal that 73.3% of GRI indicators are inherently fulfilled through operational activities; critical gaps persist in governance formalization, including the absence of dedicated sustainability structures, vague impact accountability, limited board-level oversight, and insufficient disclosure of compensation ratios. The study proposes a three-phase strategic roadmap to address these deficiencies. Despite its single-case limitation, the research offers a replicable framework for integrating ESG standards in public financial institutions, contributing to enhanced transparency, institutional accountability, and alignment with global sustainability imperatives.